Implikasi Kebijakan Sekolah Islam Terpadu Pada Peningkatan Kecerdasan Holistik Siswa SDIT Tadzkia Kota Langsa - Zulfahji; Silahuddin; Neliwati; Anna Simanjuntak; M. Alang Khairun Nizar (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the implications of integrated school policies on the enhancement of students' holistic intelligence at SDIT Tadzkia, Langsa City. Holistic education, which integrates academic, emotional, social, and spiritual intelligence, is expected to produce students who are intelligent in a comprehensive manner. Using a qualitative approach, this research employs a case study method with observation, interviews, and documentation as data collection techniques. The results of the study show that the integrated Islamic school policy at SDIT Tadzkia has a significant impact on the development of students' holistic intelligence. The integration of religious education with the academic curriculum strengthens students' character, while the development of students' social and emotional skills is also enhanced through extracurricular activities and project-based learning. Furthermore, the strengthening of spiritual intelligence supports the formation of students' noble character. The implication of this research is that integrated school policies can serve as an effective model in creating comprehensive and balanced education, which not only focuses on academic achievement but also on the development of character and life skills.